Curcumin sensitizes prostate cancer cells to radiation partly via epigenetic activation of miR-143 and miR-143 mediated autophagy inhibition. (9th August 2017) - Liu, Jianbo; Li, Min; Wang, Yuewei; Luo, Jianchao
Abstract: Curcumin has been reported as a radiosensitizer in prostate cancer. But the underlying mechanism is not well understood. In this study, we firstly assessed how curcumin affects the expression of miR-143/miR-145 cluster. Then, we investigated whether miR-143 is involved in regulation of radiosensitivity and its association with autophagy in prostate cancer cells. Our data showed that PC3, DU145 and LNCaP cells treated with curcumin had significantly restored miR-143 and miR-145 expression. Curcumin showed similar effect as 5-AZA-dC on reducing methylation of CpG dinucleotides in miR-143 promoter. In addition, curcumin treatment reduced the expression of DNMT1 and DNMT3B, which contribute to promoter hypermethylation of the miR-143/miR-145 cluster. Therefore, we infer that curcumin can restore miR-143 and miR-145 expression via hypomethylation. MiR-143 overexpression and curcumin pretreatment enhanced radiation induced cancer cell growth inhibition and apoptosis. MiR-143 and curcumin remarkably reduced radiation-induced autophagy in PC3 and DU145 cells. MiR-143 overexpression alone also reduced the basal level of autophagy in DU145 cells. Mechanistically, miR-143 can suppress autophagy in prostate cancer cells at least via downregulating ATG2B. Based on these findings, we infer that curcumin sensitizes prostate cancer cells to radiation partly via epigenetic activation of miR-143 and miR-143 mediated autophagy inhibition.